Dissecting Transient Burst Events. Issue 10 (October 2020) - Zich, Catharina; Quinn, Andrew J.; Mardell, Lydia C.; Ward, Nick S.; Bestmann, Sven
Abstract : Increasing efforts are being made to understand the role of intermittent, transient, high-power burst events of neural activity. These events have a temporal, spectral, and spatial domain. Here, we argue that considering all three domains is crucial to fully reveal the functional relevance of these events in health and disease.